The value of user feedback: Healthcare professionals' comments to the health information provider. (12th May 2014) - Tang, David Li; Bouthillier, France; Pluye, Pierre; Grad, Roland; Repchinsky, Carol
<x xml:space="preserve">Abstract</x> The construct of value is highly relevant to information. For research on the value of information, Saracevic and Kantor (1997) proposed a framework from a value perspective in philosophy. In this report, we substantiate the framework with an updated review of the literature and demonstrate its applicability to understanding the value of user feedback as one type of information. Our field study, in the setting of a health information provider whose information products serve thousands of Canadian healthcare professionals, provides an example of how this value‐of‐information framework can be operationalized for an organization. In addition to the theoretical and methodological contributions, this research adds to the literature by documenting the way that textual feedback data were used to optimize the content of an information resource. This contrasts with published studies that only dealt with the use of quantitative feedback by information providers not involved in content production.